DERMATOLOGICAL MANIFESTATIONS DUE TO TOXINS WITH SPECIAL REFERENCE TO VISHA - Kamal, Gopendra Chandra; Bharati, Ashwini Kumar S; Gururaj, Chaitra H (International Journal of Research -GRANTHAALAYAH, 2018)
Background: Ayurveda treatises are collection of vast knowledge regarding medical and environmental aspects. It has a separate branch called Agada Tantra which deals with the toxicological aspects. We aim to evaluate this knowledge regarding dermatological manifestation due to Visha (toxins) vis-à-vis contemporary knowledge. Method: The references available regarding the different types of poison and their dermatolgical manifestations in classical text were studied and compared with the available information in the contemporary medical literatures. Results: The term Visha and its types incorporates all kind of toxins. Initially, exposure to sthavara visha manifests into contact dermatitis and jangama visha manifests into contact urticaria. Dooshivisha and gara visha can be understood in terms with pesticide exposure, cosmetic toxicity, occupational exposures etc. Conclusion: The dematological manifestations play clear cut role in diagnosis and prognosis. The abundant reference in Ayurveda literatures regarding same is useful at exploring the causative factors through toxicological aspect.